Efficacy of hematopoietic stem cell formultiple sclerosis, an evidence based meta-analysis - Li, C; Feng, J; Chen, S; He, Y (Cellular and Molecular Biology, 2016)
Multiple sclerosis (MS) is thought to be a serious autoimmune disease. However, few therapy method was efficient for MS. The hematopoietic cell transplant (HCT) has been reported for a long time and can be used for MS. The clinical trials consisted of small samples and gave confusing results. This systematic review and meta-analysis aims to estimate the effects of HCT for adults with MS. We searched the database of CNKI, PUBMED, EMBASE, WEB of SCIENCE and the Cochrane Center Register of Controlled Trials to find initial studies and selected the appropriate researches included in the meta-analysis based on the inclusion and exclusion criteria. I2 was used to evaluate the heterogeneity and meta-regression was used for finding the source. Random effort model was performed to pool the data and funnel plot was drawn to determine publication bias. Six or eight single-arm clinical trials studies were included. The I2 value was 0.77 and 0.93, suggesting a heavy heterogeneity between studies. However, meta-regression analysis did not find the source of heterogeneity in which the publication country and follow up time were the influencing factors. Compared with baseline, the EDSS score of MS patients after HCT has a statistical decrease of 0.62 (95% CI 0.14, 1.10) at the 12th month and 1.26 (95%CI: 0.38, 2.14) at the follow up time ending point respectively. Available evidence suggests some clinical benefits of HCT combined with immunotherapy on MS. Due to wide confidence intervals that are characteristics of small evidence bases, further investigations to provide enough baseline information according to the RCTs are needed for further analysis, such as subgroup analysis and meta-regression analysis.